Work Motivation On Lecturer Achievement: Job Satisfaction As Mediating Variables - Titin Dunggio (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2022)
This study focused on seeing the effect of mediation of job satisfaction between competency and motivation towards lecturer achievement and also partially tested both variables. The object of this study was lecturers at universities in Gorontalo, with 100 respondents by spreading questionnaires online. This study also uses the structural equation technique with data analysis using SEM-PLS. The results showed that competency variables have a positive and significant influence both partially and mediation of job satisfaction to lecturer achievement. This research can be a reference for universities in looking at competency and motivation relationships through mediating job satisfaction towards lecturer awards to be able to take the right policies. This research in the design is static, the model that we developed based on empirical studies and testing that is only limited to putting together a simple relationship related to competency variables and motivation as variables that can affect lecturer achievement by the mediation of job satisfaction variables.